دراسة أفلام رقيقة من أكسيد القصدير المشاب بتراكيز مختلفة من الفلور F:SnO2 (Latakia University Journal -Basic Sciences Series, 2018)
تم ترسيب أفلام رقيقة شفافة من أكسيد القصدير النقي والمشاب بالفلور  بتراكيز مختلفة للاشابة بنسب وزنية ضمن المجال (5-20 wt%) على قواعد من الزجاج العادي بتقنية البخ الحراري Spray pyrolysis باستخدام محاليل من كلوريد القصدير ذي الصيغة  وفلوريد الأمونيوم . أكدت دراسة انعراج الأشعة السينية أن الأفلام المحضرة متعددة التبلور تملك بنية بلورية (Tetragonal) تنتمي إلى المجموعة الفراغية .  تتوجه الأفلام النقية وفق المستوي (211) بينما يتغير هذا التوجه للأفلام المشابة إلى المستوي (200). تم حساب المجال المحظور للأفلام حيث لوحظ زيادة في طاقة المجال المحظور مع زيادة تركيز الفلور حتى القيمة 15Wt%. وبلغت أقل مقاومة نوعية عند التركيز15Wt%، مما يدل على أنه التركيز الأمثل للحصول على خصائص بنيوية وضوئية وكهربائية جيدة. Thin films of fluorine-doped tin oxide (SnO2:F) on glass substrates were deposited by spray pyrolysis technique using (SnCl2:2H2O) and ammonium fluoride (NH4F) as precursors with the various fluorine doping levels ranging from (5 to 20) wt%. X-ray diffraction (XRD) studies revealed that the films have Tetragonal structure S.G : . It revealed that the undoped films grow along the preferred orientation of (211), whereas all the doped films grow along (200). The band gap energy was calculated. Eg values were found to initially increase with increasing the fluorine content up to 15 wt.%.  The minimum resistivity were observed for films doped with 15 wt.% . So, it is optimal concentration for getting a good structural, optical and electrical properties.